DaSI KPK Sebagai Pembiasaan Karakter Antikorupsi Dalam Pembelajaran IPS - Wahyu Purwanto (Jurnal Lingkar Mutu Pendidikan, 2021)
The purpose of this research is to determine the effect of students analytical skills on prioritizing needs as a habituation of anti-corruption character. One solution to strengthening anti-corruption character education is the application of the DaSi KPK in social studies learning. DaSi KPK is a learning tool which is an acronym for the Priority Needs Card Presentation Media. This study used an experimental method with the design of the one group pre-test-post-test. While the data analysis technique used is the t test. The results showed that there was a significant effect of the application of the DaSi KPK on the ability of students to understand and analyze the priority scale needs as strengthening the anti-corruption character in social studies subjects with a significance level of 0.014. The hope is that social studies learning will be more meaningful and strengthening the anti-corruption character with the KPK will be remembered by students all the time